SCHOOL MANAGEMENT STRATEGIES IN IMPROVING THE QUALITY OF EDUCATION WITH LEADING PROGRAMS BASED ON ISLAMIC BOARDING SCHOOLS - Imam Tabroni; Ismiati Ismiati (Lembaga Pengembangan Kinerja Dosen, 2021)
The quality of education is measured through the quality of education services provided in schools. The quality is described through the mission and vision as well as the objectives of the learning programs proposed to the community as users of educational services provided by schools. In developing and improving the quality of education, the role of the principal is very important, because the principal makes the strategy so that the learning process in accordance with the learning objectives and targets can be achieved effectively and efficiently.The research was conducted at SMA AL-Muhajirin 2 Purwakarta which implemented a superior program based on pesantren, in developing and increasing students' knowledge of religious and world sciences. The study used descriptive qualitative methods to find real data, researchers conducted in-depth observations and interviews to find out the concept of the flagship program at SMA AL-Muhajirin 2 Purwakarta in improving the quality of education.